In situ chondrogenic differentiation of bone marrow stromal cells in bioactive self-assembled peptide gels - Kim, Ji Eun; Kim, Soo Hyun; Jung, Youngmee (SOC BIOSCIENCE BIOENGINEERING JAPAN, 2015)
Articular cartilage is a specific tissue that lacks nerves and blood vessels and has limited self-repair abilities. Accordingly, it is necessary to develop new technology for the regeneration of cartilage to overcome therapeutic limitations. Recently, there have been several studies investigating the use of peptide hydrogel scaffolds, which are biocompatible and have low immunogenicity, for cartilage tissue engineering. In this study, we used self-assembled peptide hydrogels with repeating peptide sequences and bioactive motifs at the end of repeating sequences, which are collagen mimetic peptides (CMPs). CMPs that have a unique collagen-like triple helical conformation have been shown to associate with collagen molecules and fibers via a strand invasion process. In order to confirm the biological activities of the modified bioactive peptide hydrogels, the role of functional motifs in in situ chondrogenic differentiation of rabbit bone marrow stromal cells (rBMSCs) was examined. To compensate for the weaker mechanical properties of peptide hydrogels, we used poly (L-lactide-co-caprolactone) (PLCL) scaffolds, which were loaded with the self-assembled peptides into which the bioactive motifs had been incorporated. Then, we performed in vitro and in vivo analyses with the rBMSC/PLCL-peptide hydrogel complexes. The results indicated that the secretion of a cartilage-specific extracellular matrix and gene expression concerned with chondrogenic differentiation were increased by CMP motifs. In conclusion, it was confirmed that CMP-modified self-assembled peptide hydrogels could effectively enhance chondrogenic differentiation in situ, and, consequently, they could be a good biomaterial for cartilage tissue engineering. (C) 2014, The Society for Biotechnology, Japan. All rights reserved.
Keywords: MESENCHYMAL STEM-CELLS; TISSUE ENGINEERING SCAFFOLDS; CARTILAGE TISSUE; NANOFIBER SCAFFOLDS; CONTROLLED-RELEASE; PROGENITOR CELLS; HYDROGELS; REGENERATION; CULTURES; DESIGN